WARNA KULIT DAN KOMPOSISI KIMIA BUAH ASAM GELUGUR (Garcinia atroviridis Griffith et Anders.) PADA TINGKAT KEMATANGAN YANG BERBEDA - Fathia Rahmadini; Elisa Julianti; Zulkifli Lubis (AGROINTEK, 2020)
Gelugur acid (Garcinia atroviridis) is a fruit with high citric acid content so that it can be used as a source of antioxidants. This research was aimed to study the effect of fruit maturity on the color and chemical composition of gelugur fruit. Gelugur acid fruits with the different maturity level such as unripe, half-ripe, and ripe were analyzed for color, moisture content, ash content, total acid, total dissolved solids, and citric acid levels.  The results showed that fruit maturity had a significantly different effect (P 0.05) on color, moisture content, ash content, total acid, total dissolved solids, and citric acid levels. The color of fruit which is stated by oHue has a value of 71.6149-86.1362, including the yellow-red category. The higher the level of maturity, the lower the value of oHue which indicates the color of the fruit more yellow. Moisture content, ash content, and total dissolved solids increase with increasing maturity, but total acid and citric acid levels decrease with increasing fruit maturity. The highest levels of citric acid were obtained in raw fruit at 6.22%.